Macrophages Demonstrate Guanylate-Binding Protein-Dependent and Bacterial Strain-Dependent Responses to Francisella tularensis - Mohammadi, Nasibeh; Lindgren, Helena; Yamamoto, Masahiro; Martin, Amandine; Henry, Thomas; Sjöstedt, Anders (Frontiers in Cellular and Infection Microbiology, 2021)
Francisella tularensis is a facultative intracellular bacterium and the etiological agent of tularemia, a zoonotic disease. Infection of monocytic cells by F. tularensis can be controlled after activation with IFN-γ; however, the molecular mechanisms whereby the control is executed are incompletely understood. Recently, a key role has been attributed to the Guanylate-binding proteins (GBPs), interferon-inducible proteins involved in the cell-specific immunity against various intracellular pathogens. Here, we assessed the responses of bone marrow-derived murine macrophages (BMDM) and GBP-deficient BMDM to F. tularensis strains of variable virulence; the highly virulent SCHU S4 strain, the human live vaccine strain (LVS), or the widely used surrogate for F. tularensis, the low virulent F. novicida. Each of the strains multiplied rapidly in BMDM, but after addition of IFN-γ, significant GBP-dependent control of infection was observed for the LVS and F. novicida strains, whereas there was no control of the SCHU S4 infection. However, no differences in GBP transcription or translation were observed in the infected cell cultures. During co-infection with F. novicida and SCHU S4, significant control of both strains was observed. Patterns of 18 cytokines were very distinct between infected cell cultures and high levels were observed for almost all cytokines in F. novicida-infected cultures and very low levels in SCHU S4-infected cultures, whereas levels in co-infected cultures for a majority of cytokines showed intermediate levels, or levels similar to those of F. novicida-infected cultures. We conclude that the control of BMDM infection with F. tularensis LVS or F. novicida is GBP-dependent, whereas SCHU S4 was only controlled during co-infection. Since expression of GBP was similar regardless of infecting agent, the findings imply that SCHU S4 has an inherent ability to evade the GBP-dependent anti-bacterial mechanisms.